Molecular Modeling and In Vitro Evaluation of Thioureas and Arylthioureas as Urease Inhibitors - Fabris, Marciéli; Camargo, Priscila G.; Silva, Mariana L.; Lima, Camilo H. S.; Albuquerque, Magaly G.; Rodrigues, Carlos R.; Nascimento-Júnior, Nailton M. [UNESP]; Bispo, Marcelle L. F. (American Chemical Society (ACS), 2025)
Ureases are metalloenzymes found in plants, algae, fungi, and bacteria that are responsible for hydrolyzing urea into carbamate and ammonia. The bacterium Helicobacter pylori, which is associated with gastrointestinal disorders, produces large amounts of urease to neutralize stomach acidity. The rising antibiotic resistance of H. pylori presents a significant challenge for eradication efforts, highlighting the need for novel therapeutic strategies. In this study, we explored the LaSMMed chemical library to identify new urease inhibitors. Virtual screening identified six thioureas derived from cinnamic acid (LaSMMed 37-46), demonstrating urease inhibition rates ranging from 13% to 82%. The most potent compound, LaSMMed 42 (%I = 82%), was selected as a lead structure for designing a new series of arylthioureas (LaSMMed 122-126). These derivatives exhibited impressive inhibitory activity, with 84% and 88% inhibition rates. Their IC50 values ranged from 0.464 to 0.575 mM, and their inhibition constants (ki) were between 0.080 and 0.130 mM, indicating competitive inhibition for LaSMMed 125 and mixed-type inhibition for LaSMMed 122-124 and LaSMMed 126. Molecular modeling studies provided insights into the structure-activity relationships and potential binding interactions, supporting their role as promising candidates for the development of new urease-targeting agents.